PENGARUH UKURAN PERUSAHAAN, SISTEM PENGENDALIAN INTERNAL, DAN KUALITAS AUDITOR TERHADAP AUDIT DELAY DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN ENERGY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Raudatul Zannah; Miswaty Miswaty; Yanzil Azizil Yudaruddin; Hairul Anam (Jurnal GeoEkonomi, 2024)
The purpose of this study is to determine the factors that affect the Delay Audit. These factors are, Company size, Internal Control System, and Auditor Quality to Delay Audit. The data used is a source that has been present both internal and external data and data can be accessed via the internet and the publication of information. The data used is the company’s financial statements published on the Indonesia Stock Exchange from 2020-2022. Data analysis method uses logistics regression using SPSS 25 as a statistical test tool.